Design an Instrument for Measuring Current Using Its Heating Effect - Seetawan, Chatchavit; Chaiyapet , Phanomphan; Seetawan, Urai (Indochina Applied Sciences, 2020)
Material science is very important to understand the design and fabrication of measuring physical properties on Science Technology Engineering Art and Mathematic (STEAM) education to create innovative idea. We designed an instrument for measuring current from heat sources of Tungsten wire, Nichrome coil, Thermistor and Thermoelectric cell from information about Thai Young Physicists’ Tournament (TYPT) 2019. It was found that the thermoelectric cell can excellently convert heat to electrical current vice versa very good correspond with theory more than Tungsten wire, Nichrome coil, Thermistor.